Fungicide baseline for mycelial sensitivity of Exserohilum turcicum, causal agent of northern corn leaf blight - De Rossi, Roberto Luis (2015)
Northern corn leaf blight, caused by Exserohilum turcicum (Et), is one of the major corn diseases which can reduce grain yield and quality. The aim of this study was to determine the mycelial sensitivity of ten Et isolates, five from Argentina and five from Brazil, to six fungicides (carbendazim, captan, fludioxinil, metalaxyl, iprodione and thiram) used in seed treatment. The inhibitory concentration (IC50) was determined by using seven concentrations of the fungicides supplemented to the agar medium. The mycelial colony diameter was measured with a digital caliper. Experimental design was completely randomized with four replicates. Data on the percent mycelial growth inhibition were analyzed by logarithmic regression and the IC50 was calculated. The fungicide iprodione was the most potent, with IC50 < 0.01 mg/L, followed by fludioxonil, IC50 0.31 mg/L, and thiram, 1.37 mg/L. Carbendazim, metalaxyl and captan were classified as non-fungitoxic, showing IC50 > 50 mg/L for all isolates. Although iprodione is the most potent fungicide, it is not used for corn seed treatment. The IC50s obtained in this study can be used as baseline for future monitoring studies of Et sensitivity to fungicides.